Perencanaan Tebal Perkerasan Kaku (Rigid Pavement) Menggunakan Metode Bina Marga 2003 Jalan Sumbermiri - Gudo Jombang - Fernando Putra.A; Titin Sundari; Totok Yulianto; Meriana Wahyu Nugroho (Jurnal Sipil Terapan, 2025)
This lesson is to construct a durable and efficient form rigid pavement by utilizing the structural analysis and material performance approach. Rigid pavement is the main choice in highway construction because of its ability to bear heavy loads and its relatively long service life. The research methodology involves structural analysis to determine the optimal thickness and type of material for rigid pavement. This structural analysis considers various factors, including the estimated traffic load, subgrade characteristics, and local environmental conditions. In addition, material performance evaluation is also carried out to select materials that are appropriate to environmental conditions and meet technical requirements. The results of this study are recommendations for rigid pavement planning that include the right thickness, optimal material type, and construction specifications that are in accordance with applicable technical standards. The results of Rigid Pavement Thickness Planning using the Bina Marga 2003 Method on the Sumbermiri - Gudo Jombang Road case study produced a concrete slab thickness of 20 cm with K-300 concrete quality. In addition, the reinforcement used has a diameter of Ø 12 mm with a distance between reinforcements of 8,5 cm.